PENGARUH SUPERVISI AKADEMIK DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SD - Sufiyadi, Uray (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to determine the effect of academic supervision and leadership of the principal on teacher competency in management of learning at elementary school in South jawai, Sambas Regency. The method of this study is a survey research with quantitative approach. Data collection techniques of this study was a questionnaire and literature review and analyzed quantitatively by means of description, test analysis, test normalytas, test linieritas, and multiple regression analysis. The results of study found that: (1) Academic supervision (X1) provides a positive and significant effect on the teacher competency in management of learning (Y) with percentage 36 % ; (2) Leadership principal on teacher (X2) provides a positive and significant effect on the teacher competency in management of learning (Y) with percentage 38 % ; ( 3) Academic supervision (X1) and Leadership principal on teacher (X2) provides a positive and significant effect on the teacher competency in management of learning (Y) at elementary school in South Jawai, with percentage 37 %.Keywords: Academic supervision, leadership, teaching performance.